A RIPENESS STUDY OF OIL PALM FRESH FRUIT AT THE BUNCH DIFFERENT POSITIONS - Rismen Sinambela (Jurnal Keteknikan Pertanian, 2020)
The paper aims to study the position of the optimum oil palm ripeness at the bunch different positions. This information is essential to complete a measurement procedure to detect oil palm fresh fruit bunch (FFB) maturity so that the detection devices can directly measure the optimal mature position as a representative of the entire FFB characteristics. In this study, the oil palm FFB (Elaeis guineensis Jacq. var. tenera) with the various ripeness stages (4 until 22 weeks after anthesis) were collected and divided from three positions, i.e., proximal, central and distal. Moreover, each fruit in each of these positions was subjected to sample preparation to identify water and oil content. The water and oil content were completed based on the oven test method and the Soxhlet extraction technique, respectively. The optimum ripeness position is determined based on the lowest water content and the highest oil content. Based on the analysis, during the process of oil palm maturation occurs a decrease in water content and an increase in oil content. In addition, the average water content of palm fruit varies greatly depending on its position based on the analysis, i.e., proximal (45.38±5.62%), central (35.30±3.34%) and distal (41.98±2.57%). The average oil content of oil palm fruit in the central position is higher oil content (25.10±1.72%) compared to the proximal (10.00±0.77%) and distal position (13.77±1.22%). We suspect that the chemical content differences of palm fruit in various positions are due to the inequality of the respiration rate and ethylene production throughout FFB. In addition, overall it can be concluded that the fruit in the central FFB position has an optimal ripeness level compared to the proximal and distal position. Thus, the measurement position recommended in evaluating palm maturity is at the central position of FFB.